2006
DOI: 10.1002/pbc.21101
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine in children with cancer in Occidental, Mexico

Abstract: CAM use in Mexican children is common, most frequently with herbal therapies. The majority perceived benefits with its usage but in most cases, the treating physician was not informed about this practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
54
3
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 26 publications
7
54
3
9
Order By: Relevance
“…The demographic factors associated with CAM use found in our study were different from those reported in previous studies [4,[9][10][11]. We found no association between CAM use and parental age, parental education level, family income, and type or stage of disease.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The demographic factors associated with CAM use found in our study were different from those reported in previous studies [4,[9][10][11]. We found no association between CAM use and parental age, parental education level, family income, and type or stage of disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Martel et al [6] reported that about half of pediatric oncology Quebec population uses at least one type of CAM. Our results are consistent with the finding of more recent studies in pediatric cancer patients that reported a prevalence of 84%, 73%, and 70% on CAM use, in United States, Taiwan, and Mexico respectively [7][8][9]. This seems to indicate an increasing prevalence of CAM use among children with cancer over time.…”
Section: Discussionsupporting
confidence: 92%
“…16 Cancer patients also tend to have positive attitudes toward CAM therapies. [17][18][19][20] Selfreported reasons for patients using CAM included wanting to be hopeful, believing that CAM is nontoxic, and desiring to feel more in control of their treatment. 21 However, many people who use CAM do not discuss this use with their doctors.…”
mentioning
confidence: 99%
“…En Turquie, une enquête réalisée auprès d'enfants atteints de cancer a montré que 51,6 % d'entre eux avaient eu recours à la MA [4]. L'utilisation de la MA est également une pratique courante chez les enfants atteints de cancer dans l'ouest du Mexique [11]. Une enquête réalisée par Neuhouser et al, dans l'État de Washington, a montré que 73 % des patients en oncologie pédiatrique ont utilisé au moins un type de MA, dont 75 % du coût a été couvert par l'assurance maladie [6].…”
Section: Discussionunclassified
“…Au Mexique, l'utilisation des plantes médicinales a été le plus souvent signalée, par opposition à l'utilisation des remèdes bioénergétiques et à la prière qui étaient rarement employées [11]. En Turquie, la modalité la plus utilisée généralement était les produits à base d'herbes tels que le thé et les repas aux herbes dans 71 % des cas [4].…”
Section: Discussionunclassified